PENGEMBANGAN APLIKASI SISTEM PEMBELAJARAN KLASIFIKASI (TAKSONOMI) DAN TATA NAMA ILMIAH (BINOMIAL NOMENKLATUR) PADA KINGDOM PLANTAE (TUMBUHAN) BERBASIS ANDROID - Didik Kurniawan; Aristoteles Aristoteles; Ahmad Amirudin (Jurnal Komputasi, 2015)
Biology is part of science that have special characteristics different from other sciences, in terms of objects, issues and methods as well as having many terms and have the object form of the Kingdom (kingdom): Animalia (animal’s world), Plantae (plant’s world), Monera, Protista, and Fungi. Object numbering thousands of types into its own difficulties to learn it. One way to make it easier to learn it is grouping or classification of organism is called Taxonomy and the scientific name is called Binomial Nomenclature. In this study, to learn the classification and scientific nomenclature, then created taxonomy’s application based on Android, which aims to facilitate students in classifying organism consist of Kingdom, Sub Kingdom, Super Division, Division, class, Sub class, Ordo, Family, Genus, and species. This application is designed and then implemented using the Java programming language for Android, MySQL and Web Server to manipulate the data that is needed, and updates the database periodically. The results of data test using Equivalence Partitioning test shown the application functionate well according to the analysis. In addition, based on questionnaire data, that the application is a user friendly application (with an average value of 4,17 / good), and interactive (with an average value of 4,08 / good).Keywords : Android, Application, Binomial Nomenclature, Taxonomy.